Eliciting local ecological knowledge and community perception on fishlike in Taal lake through participatory approaches - Magcale-Macandog, Damasa B.; de la Cruz, Christian Paul P.; Edrial, Jennifer D.; Reblora, Marlon A. (2014)
Aquaculture of tilapia (Orechromis spp.) and bangus or milkfish (Chanos chanos) is a predominant activity in Taal Lake since 1975. Participatory Rural Appraisal (PRA) was conducted to collect and synthesize indigenous knowledge and perceptions regarding environmental conditions and fishkills in Taal Lake. Specifically, this study aimed to document anecdotes on land- and lake-use changes through time, commodity shifts and utilization, technological flow, and environmental phenomena. The community's perceptions on probable causes of fishkills were also elicited. Finally, the people's view on the different internal and external factors linked to environmental management as well as their proposed solutions to problems were accounted and analyzed.

The major trends and changes in natural resource utilization, urbanization, terrestrial and aquatic livelihood activities, and occurrence of fishkill in th four municipalities in the past seven decades were illustrated using Timeline activity. Increase in human population is the major driver of changes in the natural resources of these municipalities. The local communities in the four municipalities depend on agricultural farming and fish-based activities in Taal Lake for their livelihhod.

The various factors involved in the occurence of fishkill in Taal Lake could be categorized into environmental (climatic and volcanic) and anthropogenic factors. Oxygen depletion, volcanic activity, lake overturn, sudden changes in water color, seasonal changes, wind, hydrothermal vents, poor water quality, improper aquaculture practices, and various forms of pollution-generating anthropogenic activities were cited to have influenced the occurence of fishkills.

The devastation brought by fishkill events prompted the community to formulate solutions based on experiences, knowledge of aquaculture industry, and the physical conditions of the lake. The cage operators, for instance, conduct oxygenation of fish cages when low dissolved oxygen (DO) is observed and during transfer of fish cages to other areas. In addition, efforts towards-efficient aquaculture practices such as continuous reduction and systematic arrangement of fish cages in the respective zones, reduced stocking density and feeding rates in fish cages, and proper disposal and management of wastes from domestic, industrial and agricultural (poultry and piggery) sources are the suggested solutions to avoid fishkill. The response of the community to reduce the impact of fishkill is anchored on local ecological knowledge, technology, governance and vigilance.
Keywords: Fish kills; Water - Pollution; Taal Lake